2013
DOI: 10.1002/sm2.16
|View full text |Cite
|
Sign up to set email alerts
|

Is Female Sexual Dysfunction Related to Personality and Coping? An Exploratory Study

Abstract: IntroductionSexual disorders impact up to 43% of women. However, the relationship between sexual dysfunction and psychological variables such as personality traits and coping mechanisms is not well understood.AimTo examine personality domains and coping strategies utilized by women with sexual dysfunction in a clinical sample.MethodsPatients seeking care for female sexual dysfunction (FSD) from a sexual medicine specialist were identified using International Classification of Diseases, Ninth Revision codes. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…Our institution conducted a similar study of personality and sexual symptoms in a sample of women presenting for diagnosis and treatment of sexual dysfunction [9]. In that report, similar associations were identified between extraversion and sexual function.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Our institution conducted a similar study of personality and sexual symptoms in a sample of women presenting for diagnosis and treatment of sexual dysfunction [9]. In that report, similar associations were identified between extraversion and sexual function.…”
Section: Discussionmentioning
confidence: 64%
“…Moreover, previous history of a traumatic sexual event or absence of emotional intimacy may also contribute to the sexual dysfunction [8]. Data investigating relationships between sexual function and other psychological influences, such as personality traits and coping mechanisms, do suggest a link between the personality trait of introversion and not being open to new experiences with sexual dysfunction [9]. These associations have been noted in clinical cohorts and the general population but often sample a population outside of the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, 68% do not pay attention to their sexual dysfunction because of their busy life conditions. As far as coping processes are concerned two studies revealed that emotional support, openness and positive coping strategies are followed by lower stress levels and are correlated with better orgasm and higher sexual satisfaction while introversion and negative coping strategies induce high distress (Crisp et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…IIEF-5 scores range from 5 to 25. The presence and severity of ED was classified based on the IIEF-5 total score into absent (421), mild (17)(18)(19)(20)(21), mild/moderate (12)(13)(14)(15)(16), moderate (8)(9)(10)(11) and severe (o8). The psychometric properties of the Iranian version of the IIEF-5 have been previously demonstrated.…”
Section: Methodsmentioning
confidence: 99%
“…To adapt and cope with the distressing situation or event, they apply a variety of coping strategies, 1,2,17 some of which have shown to be beneficial, whereas others tend to act dysfunctionally. 18 Religious coping is one such beneficial strategy and is considered an active coping mechanism frequently used in individuals suffering from all sorts of bodily disabilities 1, 19 and often leading to a higher quality of life. The use of such positive religious coping strategies might be similarly helpful in patients with SCI when being confronted with injury-related sexual impairment.…”
Section: Introductionmentioning
confidence: 99%